Unbelievably deep: a chronological assessment of the Hells Midden site (5MF16), Castle Park, Colorado - Little, Spencer T., author; LaBelle, Jason M., advisor; Van Buren, Mary, committee member; Cooperman, Matthew, committee member (Colorado State University. Libraries, 2024)
During the 1940s, the University of Colorado Museum of Natural History conducted archaeological investigations of sites in the Castle Park region of the Yampa River. One of these sites, Hells Midden, was recognized early in this work as a significant site for the depth of deposits and their ability to provide a sequence of occupation within this region of the Yampa Canyon where many Fremont sites had been recently described. The cultural stratigraphy at this site, exceeding four meters in depth, was expected to provide a chronological sequence which could be used for relative dating of other sites in the region. Intensive excavation of the site in 1948 and '49, and smaller excavations in 1940 and '47, revealed an intact stratigraphic sequence at the site with relatively high densities of material deposits. Despite recognition of the site's potential, little work has been done with the assemblage since the initial curation and reporting. This thesis summarizes the results of a reanalysis of the Hells Midden assemblage. Research goals for this project were derived from questions the initial archaeologists had about these deposits: how old are they?, and how did settlement strategy expressed at the site change through time? The results of thirteen radiocarbon dates of the assemblage show a deep sequence of occupation, beginning intensively in the early Middle Archaic era (from a depth of 350 cmbs) and continuing through the Fremont occupations; an absence of dates was noted for the Late Archaic era despite contiguity of the stratigraphy. Fremont occupations were shown to agree with the sequence secured through previous radiometric work at nearby sites. For the second question, a comparison of the assemblage collected from each excavated context in 1948 and '49 was conducted by ranking multiple quantifiable metrics derived from artifactual analysis. These data, when compared with notes of the excavators and description of features through much of the site's vertical extent, suggest a relatively intensive use of this site throughout the period represented by the radiocarbon sequence, with a marked increase in the sedentism expressed by inhabitants during the Formative era Fremont occupations. The sum of these results offers insight into the Hells Midden site which makes it ripe for comparison to the regional archaeological record.
Keywords: Dinosaur National Monument; Fremont archaeology; Northern Colorado Plateau; formative transition; Castle Park Colorado; Hells Midden